Invisible Security Ink Based on Water‐Soluble Graphitic Carbon Nitride Quantum Dots. (19th January 2016) - Song, Zhiping; Lin, Tianran; Lin, Lihua; Lin, Sen; Fu, Fengfu; Wang, Xinchen; Guo, Liangqia
Abstract: Stimuli‐responsive photoluminescent (PL) materials have been widely used as fluorescent ink for data security applications. However, traditional fluorescent inks are limited in maintaining the secrecy of information because the inks are usually visible by naked eyes either under ambient light or UV‐light illumination. Here, we introduced metal‐free water‐soluble graphitic carbon nitride quantum dots (g‐CNQDs) as invisible security ink for information coding, encryption, and decryption. The information written by the g‐CNQDs is invisible in ambient light and UV light, but it can be readable by a fluorescence microplate reader. Moreover, the information can be encrypted and decrypted by using oxalic acid and sodium bicarbonate as encryption reagent and decryption reagent, respectively. Our findings provide new opportunities for high‐level information coding and protection by using water‐soluble g‐CNQDs as invisible security ink.